A comparative study and correlation between preoperative computed tomogram and endoscopic sinus surgery in chronic rhinosinusitis - John, Mithra Sara; Pillai, N. Gopinathan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic rhinosinusitis (CRS) with its classical symptoms of nasal obstruction, nasal discharge, and headache is relatively a common disease in otorhinolaryngology practice. The objectives of the present study was to correlate the operative findings in such patients with the CT findings, using the Perioperative sinus endoscopy (POSE) scoring system and to correlate the maximum scores obtained in the POSE scoring system and Lund-Mackay scoring system. Methods: A prospective study was conducted from January 2014 to March 2015 in 50 patients suffering from chronic rhinosinusitis who underwent endoscopic sinus surgery in the age group of 36-60 years of age. Results: Agger nasi cells were the most common wandering ethmoid cell detected (90%) followed by various types of frontal cells (54%), Haller cells (26%) and least commonly Onodi cells (12%). Almost perfect agreement was obtained for rest of the criteria which included middle turbinate status, ethmoid cavity mucosal edema and ethmoid cavity polypoid change. Lund-Mackay scoring system was used to score findings in the CT scan and POSE scoring system used to score peroperative findings in the study and this study reveals excellent correlation (Pearson correlation value of 0.879). Conclusions: Novel POSE scoring is a new entity which has the potential to be a valid system to score preoperative and perioperative findings. In the current study POSE scoring shows excellent correlation with Lund Mackay scoring which is an established scoring system used in the evaluation CT scan.